2005
DOI: 10.1055/s-2005-858194
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich von kontrastmittelunterstützter Low-Mechanical-Index(Low-MI)-Sonographie und nativer B-Mode-Sonographie bei der Differenzierung von Synovitis und Gelenkerguss bei Patienten mit rheumatoider Arthritis

Abstract: Contrast-enhanced low-MI sonography is superior to non-enhanced B-Mode sonography in differentiating synovitis and joint effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Although color Doppler ultrasound (CDUS) imaging allows the detection of vascularity, 1519 its ability to detect slow flow and flow in small vessels is limited. Compared with unenhanced power Doppler ultrasound, contrast-enhanced ultrasound (CEUS) has demonstrated a better ability to characterize the vascularization in the inflamed synovium, 20 because the contrast agent 21 not only improves the detection of the color signal and the extension of vascularization, 22,23 but also allows the quantitative assessment of inflammation. 24…”
Section: Introductionmentioning
confidence: 99%
“…Although color Doppler ultrasound (CDUS) imaging allows the detection of vascularity, 1519 its ability to detect slow flow and flow in small vessels is limited. Compared with unenhanced power Doppler ultrasound, contrast-enhanced ultrasound (CEUS) has demonstrated a better ability to characterize the vascularization in the inflamed synovium, 20 because the contrast agent 21 not only improves the detection of the color signal and the extension of vascularization, 22,23 but also allows the quantitative assessment of inflammation. 24…”
Section: Introductionmentioning
confidence: 99%
“…[43] Apart from synovitis, other specific histological features of inflammatory arthritis, such as bursal involvement, tendon lesions, and bone erosions, can also be detected by CEUS.…”
Section: Sonographic Findings and Histopathologic Features Of Contrasmentioning
confidence: 99%
“…And, CEUS did better than B-mode US, in differentiating synovitis and joint effusions, by demonstrating enhancement pattern of intra-articular vascularization in synovitis. [43] Another research conducted by a group of German scientists, performed CEUS, PDUS, and conventional US in the patients of RA, and evaluated the efficacy of these methods, using MRI results as the standard. A higher correlation rate of CEUS with MRI scoring was demonstrated in this study, which indicated a superior sensitivity of CEUS in detecting synovitis.…”
Section: Comparisons With Other Imaging Techniquesmentioning
confidence: 99%